A Review of Android Apps for Smoking Cessation. (4th February 2014) - Bennett, Melanie E.; Toffey, Kristin; Dickerson, Faith; Himelhoch, Seth; Katsafanas, Emily; Savage, Christina L.G.
Abstract : Introduction: The use of applications (apps) on smartphones and tablet devices is a fast growing component of health behaviour change efforts, including smoking cessation. While the content and utility of iPhone apps for smoking cessation have been systematically reviewed, Android apps have not been examined. Aims: This study reviewed and evaluated free Android apps for smoking cessation available for download from Google Play and Amazon's USA homepage in January 2013. Methods: Apps were reviewed; those targeting smoking cessation were identified and examined to ensure that they targeted tobacco smoking and were focused on quitting. Remaining apps were independently rated by three reviewers for 24 clinical strategies for smoking cessation. Results: Overall, 284 free apps were identified using the search terms 'quit smoking', 'smoking cessation', and 'stop smoking'; 113 apps that targeted smoking cessation were downloaded for further review. Of these, 21 targeted tobacco smoking and were focused on quitting. These apps had moderate to low ratings for the 24 strategies, indicating that they lacked several of the most helpful strategies for quitting smoking. The apps were strongest in helping users track the number of cigarettes smoked. None connected users to on-line sources of support, referred users to smoking cessation counselling, or recommended the use of nicotine replacement therapies. Conclusions: While Android apps for smoking cessation have some strengths, they would benefit from incorporating a broader range of strategies for helping people quit smoking.